Nearly Three Centuries of Lava Flow Subsidence at Timanfaya, Lanzarote - Victoria Purcell; Eoin Reddin; Susanna Ebmeier; Pablo J. González; Andrew Watson; Yu Morishita; John Elliott (Geochemistry, Geophysics, Geosystems, 2022)
Abstract The 1730–1736 eruption on Lanzarote was one of the most significant volcanic eruptions to occur on the Canary Islands, with lavas covering over 200 km2. Globally, it is volumetrically the third largest known subaerial basaltic fissure eruption in the past 1,100 years. Here we use Sentinel‐1 and ENVISAT interferograms on both ascending and descending orbits to construct a time series of line‐of‐sight surface displacements and calculate linear vertical deformation rates. We resolve a constant subsidence rate of about 6 mm/yr associated with an area of ∼20 km2 within the central and western portion of the Timanfaya lava flows relative to the rest of the island. This is consistent over the 28‐year period (1992–2020) covered by the Sentinel‐1 and ENVISAT data when combined with the previously published European Remote‐Sensing Satellite data. Time series constructed using Sentinel‐1 short interval interferograms have previously been shown to suffer systematic biases and we find that by making longer period interferograms these biases can be mitigated (when compared against an averaged stack of 1‐year interferograms). Cooling‐driven contraction of an intrusion would require improbably large sill thickness to achieve the observed subsidence rates. Our observations are consistent with the cooling of lavas on the order of one hundred meters, twice as thick as previous estimates, which suggests overall lava volume for this eruption may have been underestimated. This is also evidence of the longest duration of lava flow subsidence ever imaged which indicates that these cumulative thick flows can continue to deform significantly even three centuries after emplacement.